Slipdisc: a versatile sample preparation platform for point of care diagnostics. Issue 56 (12th July 2017) - Banerjee, I.; Salih, T.; Ramachandraiah, H.; Erlandsson, J.; Pettersson, T.; Araújo, A. C.; Karlsson, M.; Russom, A.
Abstract : A novel POC sample preparation technology, "Slipdisc", based rotational slipchip technology is presented. In operation, the hand-winded slipdisc platform uses a unique clockwork mechanism to manipulate minute amount of liquids. Abstract : We report a microfluidic sample preparation platform called "Slipdisc" based on slipchip technology. Slipdisc is a rotational slipchip that uses a unique hand-wound clockwork mechanism for precise movement of specially fabricated polycarbonate discs. In operation, the microchannels and microchambers carved on the closely aligned microfluidic discs convert from continuous filled paths to defined compartments using the slip movement. The clockwork mechanism introduced here is characterised by a food dye experiment and a conventional HRP TMB reaction before measuring lactate dehydrogenase (LDH) enzyme levels, which is a crucial biomarker for neonatal diagnostics. The colorimetry based detection of LDH was performed with an unmodified camera and an image analysis procedure based on normalising images and observing changes in red channel intensity. The analysis showed a close to unity coefficient of determination ( R 2 = 0.96) in detecting the LDH concentration when compared with a standard Chemical Analyser, demonstrating the excellent performance of the slipdisc platform with colorimetric detection. The versatile point of care sample preparation platform should ideally be suited for a multitude of applications at resource-limited settings.